Nanoliposomes as delivery system for anthocyanins: Physicochemical characterization, cellular uptake, and antioxidant properties. (March 2021) - Sun, Yue; Chi, Jinpeng; Ye, Xinqi; Wang, Shuo; Liang, Jin; Yue, Pengxiang; Xiao, Hang; Gao, Xueling
Abstract: Anthocyanins (ACNs) are a series of polyphenols found in plants with various biological activities. To overcome their instability toward external environments and provide more effective encapsulation method, anthocyanins-loaded nanoliposomes (AN) were firstly prepared by combining ethanol injection method with ultrasonication. This method was simple and safe which avoiding organic solvents. Good physicochemical characterizations of AN (0.15% w/v ACNs) including the encapsulation efficiency (EE, 91.1 ± 1.7%), mean particle size (53.8 ± 1.8 nm), ζ-potential (−42.7 ± 2.2 mV) and polydispersity index (PDI, 0.19 ± 0.02) were observed. The encapsulation of AN was confirmed by transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and fourier transform infrared (FTIR) spectroscopy. Nanoliposome encapsulation also enhanced the stability, cellular uptake and antioxidant activities of ACNs in vitro . It was demonstrated that the nanoliposomes prepared by this method were an efficient carriers for the delivery of ACNs, and the results expects to provide theories and practice guides for further applications of AN. Highlights: Ethanol injection method with ultrasonication was firstly adopted in this research. Anthocyanins-loaded nanoliposomes showed good physicochemical characterizations. Nanoliposomes enhanced the stability and cellular uptake of anthocyanins. Nanoliposomes improved antioxidant activity of anthocyanins in vitro.